An optimal system of recycling unwanted medicines by sustainable synergy of drugmakers, drugstores, customers and governments. (20th November 2022) - Luo, Yufeng; Wan, Zhong
Abstract: In order to lessen inappropriate disposal of unwanted medicines (UMs), this paper aims to design an effective system of recycling UMs in view of sustainable development. By taking into account heterogeneity of the UMs, cross-selling effect, subsidies and tax deductions from governments and participation willingness of UM holders, a new bi-level programming model is built to formulate such a recycle system with reflecting of sustainable synergy of drugmakers, drugstores, customers and governments in the framework of the Stackelberg game. In this model, the amount of recycled UMs is treated as an endogenous variable, depending on proportion of the selected drugstores, points-exchange incentive scheme and advertising investment. By reformulation techniques, an efficient smoothing algorithm is developed to solve the complicated model. The conducted scenario analysis validates the proposed framework of recycling the UMs and sufficiently shows its advantages over the similar ones in the literature in terms of profitability and sustainability. On average, our system can obtain a net profit margin of 24.7% and a recovery ratio of more than 50% in the scenario analysis. Main findings include: Heterogeneity of the UMs dominates distinct optimal policies of drugmakers and drugstores; Subsidies and tax deductions from governments play a critical role in promoting the recycling of UMs; The adopted strategy of reutilizing physical drugstores strategy and the cooperation between drugmakers and drugstores can significantly enhance the profitability and sustainability of the system, apart from great reduction in delivery cost and increment in customer surplus.